Effect of nanosilica injection to oil recovery factor in low porosity and permeability reservoir / Mursyidah Umar ...[et al.] - Umar, Mursyidah; Adi, Novriansyah; Novia, Rita; Ayyi, Husbani (Universiti Teknologi MARA, Perlis, 2016)
Porosity and permeability can be affected to oil recovery. Low porosity and permeability problems may cause oil flow from reservoir to wellbore becomes more difficult. A reservoir model has been prepared with 10.82% porosity and 28.8 mD Permeability using 30 mesh of homogenous sandstone. Nanosilica solution in water injection has been conducted in reservoir model. The result showed 5 % recovery factor incremental by injecting continuously 0.1% nano silica solution at 5 psi pressure. This means nanosilica injection has been successfully increase oil recovery.